Recurrent Rectal Prolapse - Naar, Leon; Sheth, Vipul; Gurland, Brooke (Clinics in Colon and Rectal Surgery, 2025)
Surgical correction is the primary treatment of external rectal prolapse. The likelihood that rectal prolapse will return is reported to be between 5 and 40% depending on a combination of technical and patient factors. In this review, we will present patient features as well as technical factors during index repair that have been shown to place patients at higher risk of recurrence. Subsequently, we will present the available data regarding the management of recurrent rectal prolapse and our approach in the care of patients with recurrence.
Keywords: rectal prolapse; rectopexy; recurrence; resection